Analisis Faktor-Faktor yang Berhubungan Dengan Quality Nursing Work Life Pada Perawat Intensive Care Unit - Thobari, Tsabitah; Ernawati, Naya; Wahyuni, Eko Sari (Jurnal Keperawatan Florence Nightingale, 2025)
The Intensive Care Unit (ICU) is a critical care setting characterized by high work demands that may adversely affect nurses’ Quality of Nursing Work Life (QNWL). Low QNWL has been associated with increased work-related stress, burnout, reduced job satisfaction, and decreased quality of nursing care. Therefore, a comprehensive analysis of the factors influencing ICU nurses’ QNWL using a multidimensional approach is essential. This study aimed to analyze factors associated with QNWL among ICU nurses at RSUD Haji, East Java Province, Surabaya. A quantitative correlational study with a cross-sectional design was conducted, involving 64 ICU nurses selected through total sampling. Data were collected using structured questionnaires assessing individual, social-contextual environment, operational, and administrative factors and were analyzed using Spearman rank correlation, Chi-square tests, and linear regression analysis. The results revealed significant associations between QNWL and social-contextual environment (p = 0.000), operational (p = 0.047), and administrative factors (p = 0.034). Among individual factors, only income showed a significant correlation with QNWL (p = 0.005). Multivariate analysis identified administrative factors as the dominant predictor of QNWL (β = 0.402; p = 0.001). These findings indicate that QNWL among ICU nurses is primarily influenced by social-contextual environment, operational, and administrative factors, with income being the only significant individual determinant. This study underscores the importance of organizational and managerial policies in enhancing nurses’ well-being and quality of work life.